Correlation coefficient analysis for yield attributes in okra (Abelmoschus esculentus) using line × tester analysis - GOSWAMI, AAKANSHA; SHARMA, ANUBHUTI; SINGH, B (The Indian Journal of Agricultural Sciences, 2015)
The present experiment on okra [Abelmoschus esculenta (L.) Moench] was conducted with 20 parents in 17 × 3 line × tester design. The experiment trial was conducted at Horticulture Research Centre, Department of Horticulture, Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, to study the correlation of that among various agronomic and economic traits for the purpose of genetic improvement and their effect in the population. The highest positive and significant genotypic and phenotypic correlation observed for green fruit yield with number of fruits per plant in parents, F1s and F2s generations. Positive and significant correlation in parents F1s observed for green fruit yield with plant height, length of first fruiting nodes, number of fruits per plant, width of fruits and number of branches per plant whereas in F2 generation the correlation for green fruit yield was positive significant with days to flowering, plant height, number of fruits per plant and length of fruits etc.